2022
DOI: 10.9734/jpri/2022/v34i33b36131
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Training-related Knee Injuries among Jazan University Students with Determining Possible Related Risk Factors

Abstract: Background: The articulating surface of the knee is the most commonly injured joint in athletes. However, there is a lack of proper prevalence and determinant estimations for knee injury among Jazan University students. Materials and Methods: This cross-sectional study aimed to determine the prevalence of knee injury among students at Jazan University, Saudi Arabia and to identify the associated risk factors. An online self-administered modified Arabic version of the Knee Injury and Osteoarthritis Outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…These anatomical variations may, in turn, affect the distribution of force and stress on the knee joint, potentially predisposing individuals to knee injuries [24]. This rationale is supported by Moafa et al [25], who suggested that university students with higher BMI values may be at a higher risk of developing knee injuries. Although a study by Gage et al [26] did not identify weight and height as significant risk factors for ACL tears, it did find that taller players were at a higher risk of ACL tears compared to their shorter counterparts.…”
Section: Discussionmentioning
confidence: 94%
“…These anatomical variations may, in turn, affect the distribution of force and stress on the knee joint, potentially predisposing individuals to knee injuries [24]. This rationale is supported by Moafa et al [25], who suggested that university students with higher BMI values may be at a higher risk of developing knee injuries. Although a study by Gage et al [26] did not identify weight and height as significant risk factors for ACL tears, it did find that taller players were at a higher risk of ACL tears compared to their shorter counterparts.…”
Section: Discussionmentioning
confidence: 94%
“…In Jazan City of Saudi Arabia, a cross sectional study was conducted on 884 students, the average percentage of knee injuries was 18%. The results of the study demonstrated that men had a higher likelihood to experience knee injuries than women by 2.7 times and that high body mass index (BMI) were related to an increased number of knee injuries (Moafa et al, 2022).…”
Section: Introductionmentioning
confidence: 99%